Work zones versus nonwork zones: Risk factors leading to rear-end and sideswipe collisions. Issue 4 (1st October 2016) - Silverstein, Claire; Schorr, Justin; Hamdar, Samer H.
ABSTRACT: Tens of thousands of vehicular collisions occur annually in work zones with nearly double the fatality risk as compared to all collisions (work zone and nonwork zone). Due to this increase in risk, this study's objective is to investigate the possible causes of work zone collisions. After reviewing previous studies, the authors examined behavioral, environmental, and roadway geometric factors to understand their influence on fatal collision type for work zones and nonwork zones. Data from the National Highway Traffic Safety Administration Fatality Analysis Reporting System database was used for years 2010 to 2012. To analyze the data, negative binomial regression and multinomial logit models were utilized. A binary probit model directly compares work zone and nonwork zone data. Results demonstrate that rear-end and sideswipe collisions are more likely to cause fatalities in work zones compared to nonwork zones. Clear conditions, daylight, and straight roads increase the likelihood of these two collision types when compared to other types such as single-vehicle collisions. These findings suggest that Intelligent Transportation Systems countermeasures (speed harmonization, vehicle-to-vehicle communications) should be investigated to encourage safer car-following and lane-changing behaviors rather than to mitigate work zone–related infrastructure challenges.